Factors influencing the life table statistics of the cassava mealybug Phenacoccus manihoti - Schulthess, F.; Baumgaertner, J.U.; Herren, H.R. (1987)
Detailed age-specific life table studies were carried out under controlled conditions to measure the effect of temperature, leaf quality ( = age), variety and plant drought stress on net production rate (R0), intrinsic rate of increase (rm) and generation time (G) of Phenacoccus manihoti Mat.-Ferr. in order to explain changes in population densities observed in the field. The developmental threshold calculated from our data and results published by various authors was 14.7°C. At 35°C all mealybugs died before reaching the adult stage. Mealybugs reared on leaves of different ages showed little differences in rm, and the higher occurrence of P. manihoti on plant tips and oldest leaves could not be explained with better nutritive value of these plant parts alone. Cassava varieties have a strong influence on the intrinsic rate of increase, which could explain differences in results published by other authors. Plant drought stress had little influence on the life table statistics, but rainfall is assumed to be a determinant factor in the dynamics of the mealybug.